Three approaches to restoration and their implications for social inclusion - Sigman, Emily; Elias, Marlène (University of Wisconsin Press, 2021)
Building on the Bonn Challenge, the UN Decade advances global restoration on an unprecedented scale. Research increasingly points to the need for greater social inclusion in restoration projects, yet the approaches that favor such inclusion remain opaque in practice. In this paper, we identify three restoration approaches that figure in the international agenda and analyze these through the lens of social inclusion. We argue that: (1) restoration aimed at bringing ecosystems back to a previous state, or “return” restoration, favors natural science at the landscape scale over social inclusion at the community scale; (2) restoration seeking to recreate functional ecosystems in locations away from where the degradation has occurred, or “reorganization” restoration, fails to adequately address historical inequities and perpetuates legacies of exploitation; and (3) “resilience” oriented restoration is promising but remains theoretical, and risks instrumentalizing marginalized communities and their lands as experimental sites for restoration. Though both “return” and “reorganize” restoration face substantial criticism, these approaches continue to play a central role in the major paradigms and practices that enliven the global restoration agenda. To improve prospects for social inclusion in the global restoration movement, we advance that the movement must evolve beyond productivity-based inclusion schemes and address the role that international initiatives play in perpetuating systems of exploitation. Finally, we argue that “resilience” restoration offers the most promising pathway towards meaningful social inclusion when it can empower community members to participate in restoration as agents of change and co-experimenters.